2009
DOI: 10.1016/j.ijheatmasstransfer.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on mechanism of critical cavitating flow in liquid jet pumps under operating limits

Abstract: a b s t r a c tThe critical cavitating flow in liquid jet pumps under operating limits is investigated in this paper. Measurements on the axial pressure distribution along the wall of jet pumps indicate that two-phase critical flow occurs in the throat pipe under operating limits. The entrained flow rate and the distribution of the wall pressure upstream lowest pressure section does not change when the outlet pressure is lower than a critical value. A liquid-vapor mixing shockwave is also observed under operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…6(a), which is similar to the liquidegas mixing shockwave proposed by Witte and Brennen [25,26]. The interface wave is instability and moves forward and backward [27], crossing which the density, velocity and pressure change sharply. Hence, there is a great pressure gradient VP appearing when the interface wave passes.…”
Section: Relationships Between Absorption Amount Q L and Outlet Presssupporting
confidence: 64%
“…6(a), which is similar to the liquidegas mixing shockwave proposed by Witte and Brennen [25,26]. The interface wave is instability and moves forward and backward [27], crossing which the density, velocity and pressure change sharply. Hence, there is a great pressure gradient VP appearing when the interface wave passes.…”
Section: Relationships Between Absorption Amount Q L and Outlet Presssupporting
confidence: 64%
“…In our previous studies, pressure coefficient distribution (C p ) is suitable to describe the inner flow details, especially when cavitation appears (Long et al, 2009). In this study, by monitoring C p , the cavitation state and the development of vapor cloud were obtained.…”
Section: Pressure Coefficient Distributionmentioning
confidence: 98%
“…Hence the inception of cavitation in CJP can be due to high shear and vortex in jet boundary (namely shearing layer). However, Long et al (2009) pointed out that adverse pressure gradient caused by the convergent suction chamber was another reason for cavitation occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the sound velocity decreases sharply as the gas fraction increases, declining to only 25 m/s at a high gas fraction. Long et al [15] investigated the critical cavitation flow in the jet pump and observed a liquid-vapor mixing shockwave. The wave front moves back and forth around the lowest pressure point at a low frequency, while the pressure fluctuation and propagation rule of the wave are not mentioned in further study.…”
Section: Introductionmentioning
confidence: 99%